A paradigm for secure object access and unrestricted mobility in distributed systems. Issue 5 (3rd September 2022) - Lopriore, Lanfranco
Abstract : In distributed architectures consisting of processing nodes, we associate a node chain with each object. The node chain connects a node named in the object identifier to the nodes reserving secondary and primary memory space for the object. No restriction exists on object movements across the network. A process can access a given object only if it holds a security gate referencing this object. The gate includes a password and the specification of an access authorisation. Gate weakening and revocation are fully supported. GRAPHICAL ABSTRACT: UF0001